Geochemical signature of the Permian-Triassic transitional environment, Pine Forest Range, Nevada - LaVine, Rhiannon (My University, 2011)
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater. This poster explains the project undertaken to gather rocks and fossils from a specific location in the Pine Forest Range in Nevada and conduct analysis on the samples to detemine environmental conditions during the Permian-Triassic transition.
This file was last viewed in Adobe Reader 10.0.1
Keywords: Chemostratigraphy--Nevada--Pine Forest Range; Geology, Stratigraphic--Permian; Geology, Stratigraphic--Triassic; Rocks--Nevada--Pine Forest Range; Pine Forest Range (Nev.)